HIV in the dialysis population: Current issues and future directions. Issue 5 (13th June 2017) - Boyle, Suzanne M.; Lee, Dong H.; Wyatt, Christina M.
Abstract: Antiretroviral therapy has significantly reduced mortality due to HIV infection, but the aging HIV‐positive patient population now faces a growing burden of comorbidity. This review describes the changing epidemiology of chronic kidney disease and end‐stage renal disease in this population, and highlights recent advances in antiretroviral therapy and kidney transplantation that directly impact the care of patients with HIV infection and end‐stage renal disease.